Implementasi Pembelajaran IPS Melalui Outing Class di TK Wanita Pui: Implementation of IPS Learning Through Outing Class in Pui Women's Kindergarten - Virda Syaripatunisa; Nur Azizah; Adi Saputra; Nuraly Masum Aprily (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
Social science is one of the important lessons for early childhood development, helping children to be able to understand how the world functions, starting from the environment they are in, culture and community. Through this learning children can develop an understanding of themselves and their relationships with others and build the social skills needed in everyday life. There are several methods for implementing social studies learning for early childhood, one of which is by using the outing class method. With this outing class method, children will get direct experience, such as visiting historical places, watching cultural performances and so on. This study uses qualitative methods with data collection techniques by observation and in-depth interviews. The results of the research that the researchers got were about the implementation of social science learning through outing classes in PUI Women's Kindergarten. Â  ABSTRAK Ilmu pengetahuan sosial merupakan salah satu pembelajaran penting untuk pengembangan anak usia dini, membantu anak untuk dapat memahami bagaimana dunia berfungsi, mulai dari lingkungan tempat mereka berada, kebudayaan dan komunitas. Melalui pembelajaran ini anak dapat mengembangkan pemahaman tentang diri mereka sendiri dan hubungan mereka dengan orang lain serta membangun keterampilan sosial yang diperlukan dalam kehidupan sehari-hari. Ada beberapa metode untuk mengimplementasikan pembelajaran IPS kepada anak usia dini, salah satunya dengan menggunakan metode outing class. Dengan metode outing class ini anak akan mendapatkan pengalaman langsung seperti mengunjungi tempat-tempat yang bersejarah, menonton sebuah pertunjukan budaya dan lain sebaginya. Penelitian ini menggunakan metode kualitatif dengan Teknik pengumpulan data dengan observasi dan wawancara mendalam. Adapun hasil penelitian yang peneliti dapatkan yaitu tentang implementasi pembelajaran ilmu pengetahuan sosial melalui outing class di TK Wanita PUI.